The immediate effects of Graston Instrument-Assisted Soft-Tissue Mobilization and self-stretching on the muscular properties of the gastrocnemius in athletes - Kang, H.-S.; Lee, J.-H. (Journal of The Korean Society of Physical Medicine, 2020)
PURPOSE: This study examined the immediate effects of Graston instrument-assisted soft-tissue mobilization (GIASTM) and self-stretching on the muscular properties of the gastrocnemius in athletes. METHODS: Thirty subjects (All in their 20 s) were distributed randomly and evenly into two groups of 15 each: GIASTM and stretching. The subjects had no history of gastrocnemius damage in the previous three months. The muscle tone, stiffness, elasticity, and mechanical stress relaxation time (MSRT) of the gastrocnemius were blind-tested. RESULTS: The GIASTM group showed significant changes in all categories, while only MSRT changed significantly in the self-stretching group after intervention. A comparison of the two groups revealed significant differences in stiffness, elasticity, and MSRT (Time required for the muscle to recover after distortion after intervention in the GIASTM group. CONCLUSION: In this study, significant decreases in muscle tone and stiffness, as well as significant increases in elasticity, were observed in the gastrocnemius of the GIASTM group. On the other hand, sSelf-stretching showed significant differences in MSRT. Therefore, GIASTM is more effective in the recovery of the gastrocnemius muscle from fatigue than self-s retching. This study suggests that GIASTM can help prevent damage to the gastrocnemius in athletes and contribute to their training and rehabilitation programs